Integrated Energy System Systems and Game Theory A Review - Arief Ramadhan; Bhima Bhima; Tio Nurtino (Pandawan Sejahtera Indonesia, 2022)
As mankind expands quickly, there is a shortage of energy worldwide. Instead of focusing on the production, transmission, and provision of a particular power source, China has proposed an To address the energy crisis, an integrated energy system is being developed. This system links energy resources and utilizes their complementary benefits. With the development of integrated energy systems, involvement and Engagement is getting increasingly difficult. Game theory, which can successfully address issues arising from multi-agent commerce, is a natural application of the System of integrated energy. This publication gives in-depth information analysis of how the integrated power system has undergone game theory analysis. Initial game situations in integrated power systems are provided, followed by a brief introduction to the evolution of integrated energy, The design and deployment of interconnected power systems issues are outlined, along with game scenarios that take into account the energy production side, supply chain, demand side, and all of these factors. Second, a summary of the fundamental for the integrated energy system, use game theory models is provided. The last topic is examined along with the challenges involved in game theory's potential application to integrated power systems. When applying the newly created game models to the integrated power system, a mixed game is recommended to solve these issues. This study should prove to be an invaluable resource for upcoming scholars in the subject.